Role of Nuclear Lamin A/C in the Regulation of Nav1.5 Channel and Microtubules: Lesson From the Pathogenic Lamin A/C Variant Q517X - De Zio, Roberta; Pietrafesa, Giusy; Milano, Serena; Procino, Giuseppe; Bramerio, Manuela; Pepe, Martino; Forleo, Cinzia; Favale, Stefano; Svelto, Maria; Gerbino, Andrea; Carmosino, Monica (Frontiers in Cell and Developmental Biology, 2022)
In this work, we studied an lmna nonsense mutation encoding for the C-terminally truncated Lamin A/C (LMNA) variant Q517X, which was described in patients affected by a severe arrhythmogenic cardiomyopathy with history of sudden death. We found that LMNA Q517X stably expressed in HL-1 cardiomyocytes abnormally aggregates at the nuclear envelope and within the nucleoplasm. Whole-cell patch clamp experiments showed that LMNA Q517X-expressing cardiomyocytes generated action potentials with reduced amplitude, overshoot, upstroke velocity and diastolic potential compared with LMNA WT-expressing cardiomyocytes. Moreover, the unique features of these cardiomyocytes were 1) hyper-polymerized tubulin network, 2) upregulated acetylated α-tubulin, and 3) cell surface Nav1.5 downregulation. These findings pointed the light on the role of tubulin and Nav1.5 channel in the abnormal electrical properties of LMNA Q517X-expressing cardiomyocytes. When expressed in HEK293 with Nav1.5 and its β1 subunit, LMNA Q517X reduced the peak Na+ current (INa) up to 63% with a shift toward positive potentials in the activation curve of the channel. Of note, both AP properties in cardiomyocytes and Nav1.5 kinetics in HEK293 cells were rescued in LMNA Q517X-expressing cells upon treatment with colchicine, an FDA-approved inhibitor of tubulin assembly. In conclusion, LMNA Q517X expression is associated with hyper-polymerization and hyper-acetylation of tubulin network with concomitant downregulation of Nav1.5 cell expression and activity, thus revealing 1) new mechanisms by which LMNA may regulate channels at the cell surface in cardiomyocytes and 2) new pathomechanisms and therapeutic targets in cardiac laminopathies.